Direct Vocabulary Instruction in Kindergarten: Teaching for Breadth versus Depth - Coyne, Michael D.; McCoach, D. Betsy; Loftus, Susan; Zipoli, Richard; Kapp, Sharon (The Elementary School Journal, 2009)
Abstract The purpose of this study was to compare 2 methods for directly teaching word meanings to kindergarten students within storybook read‐alouds that varied in instructional time and depth of instruction along with a control condition that provided students with incidental exposure to target words. Embedded instruction introduces target word meanings during storybook readings in a time‐efficient manner. Extended instruction is more time intensive but provides multiple opportunities to interact with target words outside the context of the story. Participants included 42 kindergarten students who were taught 9 target words, 3 with each method. Target words were counterbalanced in a within‐subjects design. Findings indicated that extended instruction resulted in more full and refined word knowledge, while embedded instruction resulted in partial knowledge of target vocabulary. Implications are discussed in relation to the strengths and limitations of different approaches to direct vocabulary instruction in kindergarten and the trade‐offs between instruction that focuses on teaching for breadth versus depth.
Keywords: dept.cmd; peer-reviewed

Direct Instruction of Comprehension: Instructional Examples From Intervention Research on Listening and Reading Comprehension - Coyne, Michael D.; Zipoli Jr., Richard P.; Chard, David J.; Faggella-Luby, Michael; Ruby, Maureen; Santoro, Lana E.; Baker, Scott (Reading & Writing Quarterly, 2009)
This article examines the role of direct instruction in promoting listening and reading comprehension. Instructional examples from 2 programs of intervention research focused on improving comprehension; the Story Read Aloud Program and the Embedded Story Structure Routine are used to illustrate principles of direct instruction. An analysis of these 2 approaches suggests that direct instruction principles are effective in supporting students with varied achievement levels and that these principles can be used to enhance comprehension among students at very different points in reading development. These evidence-based approaches also illustrate that direct instruction can be designed to support complex learning and the development of higher order cognitive strategies.
_eprint: https://doi.org/10.1080/10573560802683697
Keywords: dept.cmd; peer-reviewed

Answering Orientation Questions and Following Single-Step Verbal Commands: Effect on Aspiration Status - Leder, Steven B.; Suiter, Debra M.; Lisitano Warner, Heather (Dysphagia, 2009)
In the acute-care setting patients with altered mental status as a result of such diverse etiologies as stroke, traumatic brain injury, degenerative neurologic impairments, dementia, or alcohol/drug abuse are routinely referred for dysphagia testing. A protocol for dysphagia testing was developed that began with verbal stimuli to determine patient orientation status and ability to follow single-step verbal commands. Although unknown, it would be beneficial to ascertain if this information on mental status was predictive of aspiration risk. The purpose of this investigation was to determine if there was a difference in odds for aspiration based upon correctly answering specific orientation questions, i.e., 1. What is your name? 2. Where are you right now? and 3. What year is it?, and following specific single-step verbal commands, i.e., 1. Open your mouth. 2. Stick out your tongue. and 3. Smile. In a consecutive retrospective manner data from 4070 referred patients accrued between 1 December 1999 and 1 January 2007 were analyzed. The odds of liquid aspiration were 31% greater for patients not oriented to person, place, and time (odds ratio [OR] = 1.305, 95% CI = 1.134–1.501). The odds of liquid aspiration (OR = 1.566, 95% CI = 1.307–1.876), puree aspiration (OR = 1.484, 95% CI = 1.202–1.831), and being deemed unsafe for any oral intake (OR = 1.688, 95% CI = 1.387–2.054) were, respectively, 57, 48, and 69% greater for patients unable to follow single-step verbal commands. Being able to answer orientation questions and follow single-step verbal commands provides information on odds of aspiration for liquid and puree food consistencies as well as overall eating status prior todysphagia testing. Knowledge of potential increased odds of aspiration allows for individualization of dysphagia testing thereby optimizing swallowing success.
Keywords: Aspiration; Cognition; Deglutition; Deglutition disorders; peer-reviewed

Comparisons of P300s from Standard Oddball and Omitted Paradigms: Implications to Exogenous/Endogenous Contributions - McCullag, Jennifer; Weihing, Jeffrey; Musiek, Frank (Journal of the American Academy of Audiology, 2009)
Purpose: To compare the amplitude, latency, morphology, and threshold of the auditory P300 using standard oddball and omitted paradigms. Research Design: P300 waveforms were measured from the Cz electrode site. Frequent stimuli for both paradigms were 1000 Hz tone bursts. Target stimuli for the standard oddball paradigm were 2000 Hz tone bursts and an omitted stimulus, or silent gap, for the omitted paradigm. Study Sample: Fifteen bilaterally normal-hearing young adults. Results: There were significantly lower amplitudes, poorer morphology, and higher thresholds for the P300 using an omitted paradigm compared to the standard oddball paradigm. Conclusion: These results suggest that the auditory P300 could have a larger exogenous component than traditionally thought.
Keywords: Key Words Endogenous; P300; dept.cmd; exogenous; intensity effects; omitted paradigm; peer-reviewed

Book Review: Stuttering and related disorders of fluency, third edition, edward g. conture, richard f. curlee (eds.). thieme medical publishers, inc., new york, NY (2007), 372 pp., hardback - Felsenfeld, Susan (Journal of Fluency Disorders, 2009)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/030-778-443-037-132 tex.type: [object Object]
Keywords: book.review; dept.cmd

Fundamental frequency and gender identification in standard esophageal and tracheoesophageal speakers. - Bellandese, Mary H (Journal of Communication Disorders, 2009)
UNLABELLED: The purpose of this study was to determine if there was a relationship between fundamental frequency (Fo) and gender identification in standard esophageal (ES) or tracheoesophageal (TE) speakers. Twenty-three male and 20 female ES and TE speakers participated in this study. Recordings of these speakers reading the Rainbow Passage were played to 48 listeners who indicated perceived gender in a forced choice format. Fo was determined using PC-AUDED [Boston University (1991). Using PC-AUDED, Audio-editor and analyses program for the study of periodic segments. Boston: Boston University]. Seventy-nine percent of the speakers were identified correctly for gender. No significant difference was found between the number of male and female or TE and ES speakers identified correctly. A significant correlation was found between Fo and correct gender identification for the female speakers only. Results suggest that Fo plays a part in gender identification for female SE and TE speakers, however, other factors may also be important cues for gender identification in these speakers., LEARNING OUTCOMES: As a result of this activity, the participant will be able to: (1) describe the relationship between Fo and gender identification for male and female standard esophageal (SE) and tracheoesophageal (TE) speakers (2) discuss other variables that may influence gender identification in SE and TE speakers.
3 citations (Crossref) [2023-10-31] Place: United States Bellandese, Mary H. Southern Connecticut State University, New Haven, CT 06515-1355, USA. bellandesem1@southernct.edu
Keywords: *Sex Characteristics; *Speech Acoustics; *Speech Perception; *Speech; Esophageal/px [Psychology]; *Trachea; Adult; Aged; Aged; 80 and over; Female; Humans; Male; Middle Aged; Sex Characteristics; Sound Spectrography; Speech Acoustics; Speech Perception; Speech; Esophageal; Task Performance and Analysis; Trachea; Young Adult; dept.cmd

Conversational Behaviors in Youth with High-functioning ASD and Asperger Syndrome. - Paul, Rhea; Orlovski, Stephanie; Marcinko, Hillary; Volkmar, Fred (Journal of Autism and Developmental Disorders, 2009)
Twenty-nine youth with autism spectrum disorders and 26 with typical development between 12 and 18 years of age were engaged in structured interviews (ADOS). The interviews were videotaped and rated for atypical conversational behaviors by trained raters, using the Pragmatic Rating Scale (Landa et al. Psychol Med 22:245-254, 1992). The ASD group was divided into AS and HFA/PDD-NOS subgroups. Significant differences were found among groups on approximately one-third of the PRS items. These items involved primarily the management of topics and information, reciprocity, intonation, and gaze management. The only differences to reach significance between the AS and HFA/PDD-NOS group were a greater tendency for overly formal speech on the part of the AS group, and more difficulty with gaze management on the part of the group with HFA/PDD-NOS. The implications of these findings for understanding and treating conversational deficits in ASD are discussed., (C) Plenum Publishing Corporation 2009. All Rights Reserved.
173 citations (Crossref) [2023-10-31] Place: (C) Plenum Publishing Corporation 2009. All Rights Reserved.
Keywords: *Asperger Syndrome/di [Diagnosis]; *Autistic Disorder/di [Diagnosis]; *Interpersonal Relations; *Verbal Behavior; Adolescent; Asperger Syndrome; Asperger Syndrome/px [Psychology]; Asperger syndrome; Autism; Autistic Disorder; Autistic Disorder/px [Psychology]; Child; Conversation; Female; Humans; Intelligence; Interpersonal Relations; Keywords; Language Development Disorders; Language Development Disorders/di [Diagnosis]; Language Development Disorders/px [Psychology]; Male; Pragmatics; Pragmatics Conversation; Speech Acoustics; Speech Intelligibility; Verbal Behavior; Vocabulary; article; autism; behavior; clinical article; controlled study; conversation; dept.cmd; human; juvenile; peer-reviewed; priority journal; rating scale; structured interview; videotape